Numerical and experimental studies on single phase natural circulation loop using water and oil based hybrid nanofluids - Sahu, Mayaram (IIT(BHU) Varanasi, 2022)
Abstract is available in the content.
Keywords: Numerical and experimental studies; on single phase; natural circulation loop; using water and; oil based hybrid nanofluids